Compatibility of Azospirillum brasilense with Pesticides Used for Treatment of Maize Seeds - Mariana S. Santos; Artur B. L. Rondina; Marco A. Nogueira; Mariangela Hungria (International Journal of Microbiology)
Seed treatment with chemical pesticides is commonly used as an initial plant protection procedure against pests and diseases. However, the use of such chemicals may impair the survival and performance of beneficial microorganisms introduced via inoculants, such as the plant growth-promoting bacterium Azospirillum brasilense. We assessed the compatibility between the most common pesticide used in Brazil for the treatment of maize seeds, composed of two fungicides, and one insecticide, with the commercial strains Ab-V5 and Ab-V6 of A. brasilense, and evaluated the impacts on initial plant development. The toxicity of the pesticide to A. brasilense was confirmed, with an increase in cell mortality after only 24 hours of exposure in vitro. Seed germination and seedling growth were not affected neither by the A. brasilense nor by the pesticide. However, under greenhouse conditions, the pesticide affected root volume and dry weight and root-hair incidence, but the toxicity was alleviated by the inoculation with A. brasilense for the root volume and root-hair incidence parameters. In maize seeds inoculated with A. brasilense, the pesticide negatively affected the number of branches, root-hair incidence, and root-hair length. Therefore, new inoculant formulations with cell protectors and the development of compatible pesticides should be searched to guarantee the benefits of inoculation with plant growth-promoting bacteria.